1994
DOI: 10.1002/jmv.1890420303
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological studies of human herpesvirus 6 in families

Abstract: The mode of transmission of human herpesvirus 6 (HHV-6) was investigated by molecular epidemiological techniques in four families. HHV-6 was isolated from the peripheral blood of seven infants with exanthem subitum, including siblings, and from the saliva of two mothers. These isolates were examined for genetic relatedness by means of restriction enzymes analysis of purified DNA. While the profiles of the digestion patterns differed among families, they were very similar in a particular family. These results m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 24 publications
0
26
0
3
Order By: Relevance
“…The shedding of HHV-6 in the secretions of asymptomatic caretakers is thought to be a major route of transmission, while contact with infants is another possible route Mukai et al, 1994;Tanaka-Taya et al, 1996]. It has also been reported that HHV-6 may be transmitted during the intrauterine or perinatal period [Okuno et al, 1995], although transmission through breast-feeding has been disproved [Kusuhara et al, 1997;Fujisaki et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…The shedding of HHV-6 in the secretions of asymptomatic caretakers is thought to be a major route of transmission, while contact with infants is another possible route Mukai et al, 1994;Tanaka-Taya et al, 1996]. It has also been reported that HHV-6 may be transmitted during the intrauterine or perinatal period [Okuno et al, 1995], although transmission through breast-feeding has been disproved [Kusuhara et al, 1997;Fujisaki et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…HHV‐7 uses the CD4 receptor to infect and establish latency in T lymphocytes; active replication occurs in salivary glands . The principal mode of transmission for both viruses is horizontal via saliva of siblings or adult family members . Vertical spread of HHV‐6 can occur as well, either transplacentally or through inheritance from one or both parents, as HHV‐6 is integrated into the genome of 0.2–3% of the population .…”
Section: Pathogenesis and Transmissionmentioning
confidence: 99%
“…HHV-6 is one of the most widespread herpesviruses, infecting the human population with a prevalence approaching 100%. The most probable route for transmission is through saliva, either from mother to child or between children [Mukai et al 1994]. Two types (A and B) can be identified; no diseases have clearly been linked to HHV-6A infection, whereas HHV-6B is responsible for exanthema subitum.…”
Section: Human Herpesvirusmentioning
confidence: 99%